Future directions of spiritual care where spiritual care providers do not exist: a qualitative study - Nattawan Meeprasertsagool; Patiphat Anuraktham; Arthit Chaithanasarn; Itthipon Wongprom (BMC Palliative Care)
Abstract Introduction Spiritual care is a fundamental aspect of palliative care, addressing the emotional, existential, and spiritual needs of patients facing life-threatening illnesses. However, in Thailand, the integration of spiritual care into the healthcare system remains underdeveloped due to the absence of professional spiritual care providers. This study aims to explore potential models and future directions for spiritual care within the palliative care context, focusing on how such care can be provided in the absence of professional spiritual care providers. Method This study is a part of the mixed-method project Shoulders to Cry on: Care for spirituality when spiritual care providers do not exist, aimed at exploring spiritual care in settings without professional providers in Thailand. Qualitative in-depth interviews were conducted with 20 experts from palliative care, religious studies, and social work fields. The participants were recruited through purposeful sampling, and the data were analysed using inductive thematic analysis. Transcribed interviews were managed using NVivo software to identify key patterns and insights for future spiritual care models. Result The analysis resulted in the development of the S.P.I.R.I.T. model, which outlines six essential themes for the future of spiritual care: (1) Spirituality Training Programs, (2) Providers for Spiritual Care, (3) Integrating Spiritual Care into Healthcare, (4) Research and Evidence-based Practices, (5) Interdisciplinary Collaboration, and (6) Transforming Care Systems. The findings suggest establishing structured training programs and interdisciplinary collaboration are crucial for effective spiritual care delivery. Conclusion The study emphasises the need for integrating spiritual care into Thailand’s healthcare system, focusing on education, research, and collaboration between healthcare providers and religious or community figures. The S.P.I.R.I.T. model offers a framework for addressing current gaps, which could facilitate Thailand’s palliative care system in better meeting the spiritual needs of patients. Future studies should focus on establishing spiritual care education in palliative care, especially in resource-limited countries, and addressing local contextual obstacles.